Ligand field splitting energies of the hexaamminecobalt(II) ion and the hexaamminenickel(II) ion measured by a calorimetric method - Muhammmad, Badri; Jamieson, J. W. S. (N R C Research Press, 1970)
Various normal lower ammines and high-energy modifications of the lower ammines of cobalt(II) sulfate and nickel(II) sulfate have been prepared and the heats of solution in dilute ammonia have been measured for both types. For each of these ammine systems the maximum difference in heat of solution, expressed as kcal/rnole of each heptaammine, between the high-energy and the normal salts has been found to be in close agreement with the ligand field splitting energy of the hexaamminemetal(lI) ion.